Four new species of Cladorhizidae (Porifera, Demospongiae, Poecilosclerida) from the Northeast Pacific - Lundsten, Lonny; Reiswig, Henry M.; Austin, William C. (Zootaxa, 2014)
Interest in cladorhizid sponges has grown rapidly in the past 19 years since a unique feeding strategy, carnivory, was described by Vacelet and Boury-Esnault in 1995. Since that time, 31% of the 133 extant cladorhizids have been described. Previously, seven species of cladorhizid sponges were known from the Northeast Pacific. Here we describe four additional species, including two species of Asbestopluma and two species of Cladorhiza. We report on species ranges, habitat, and ecology, including one from a chemosynthetic environment that appears to be using methane-oxidizing bacteria as a nutrient source. In fact, three of the four species described here were found in chemosynthetic habitats. The presence of small crustacean prey was also documented for three of these species.